University didactic planning: an evaluation experience from ISO 9001:2000 - Navarro, Rubén Edel; Cano Couary, Guillermo (Avances en Supervisión Educativa, 2008)
The university didactic planning: A experience of evaluation from ISO norm 9001:2000At present, higher education institutions in Mexico regard certification or accreditation as an official recognition to their struggle in favour of high-quality standards in the educational offer they provide. This research article describes the analysis of the process to set up university general programmes under the ISO 9001:2000 Regulation, which aimed at identifying areas of suitable improvement detected by users.The present research was carried out in cooperation with the educational staff at the University of the Caribbean in Quintana Roo, Mexico, consisting of teachers by subject, support technicians and full-time teachers who hold masters and doctorate degrees. The compilation of data was made through the so-called instrument for users of the SIPLADI application, with a quantitative-qualitative mixed methodology.
Keywords: Educative quality; Educative evaluation; Didactic planning; Norm ISO 9001:2000